Adult attachment : a concise introduction to theory and research - Gillath, Omri; Karantzas, Gery C.; Fraley, R. Chris (Academic Press is an imprint of Elsevier, 2016)
Adult Attachment: A Concise Introduction to Theory and Research is an easy-to-read and highly accessible reference on attachment that deals with many of the key concepts and topics studied within attachment theory. This book is comprised of a series of chapters framed by common questions that are typically asked by novices entering the field of attachment. The content of each chapter focuses on answering this overarching question. Topics on the development of attachment are covered from different levels of analysis, including species, individual, and relationship levels, working models of attachment, attachment functions and hierarchies, attachment stability and change over time and across situations, relationship contexts, the cognitive underpinnings of attachment and its activation of enhancement via priming, the interplay between the attachment behavioral system and other behavioral systems, the effects of context on attachment, the contribution of physiology/neurology and genetics to attachment, the associations/differences between attachment and temperament, the conceptualization and measurement of attachment, and the association between attachment and psychopathology/therapy.